Peran Orang Tua dalam Mengenalkan Literasi Digital pada Anak Usia Dini di Dusun Ringin Desa Tlogorejo Kecamatan Sukodadi Kabupaten Lamongan - Ghozali, Muhamad Ansori; Nugroho, Rivo (J+PLUS UNESA, 2023)
Children's education can be supported by technology because the many opportunities and challenges presented by digital media can be used as a means to support children's growth and development. Parents have an important and essential role in children's development because they give children the experiences they have. The role of parents in digital literacy in early childhood and the efforts made to support parents in introducing, and guiding children to use digital media and the use of digital literacy for children in early childhood development. This research uses a qualitative approach to research with descriptive writing methods. Data collection techniques in this study are by using in-depth interviews, participatory observation, and documentation. This research shows that parental management assistance in introducing digital literacy has several results of mentoring patterns, namely increasing the number and variety of quality learning resources and expanding access to quality learning resources and their scope.